Efecto de la aplicación de algas fosilizadas y fertilizantes químicos en el rendimiento de tres variedades de papa (Solanum tuberosum L.) fripapa, superchola y chaucha, en el sector Carboncillo del cantón Saraguro - Ortega Montoya, Jessica Elena (2023)
Potato (Solanum tuberosum L.) is an important traditional crop worldwide, however, in Ecuador the last few years there have been low yields, which merits looking for alternative sources of organic fertilization to improve production, organic fertilizers such as fossilized algae are considered as a healthy and viable alternative for crops of agricultural interest. However, producers make use of chemical fertilizers to increase yields due to the low cost involved in contrast to organic fertilizers, without considering the damage caused by excessive abuse to the soil and the environment. The objective of this research was to evaluate the effect of fossilized algae in comparison with chemical fertilization based on 10-30-10 on the yield of three potato varieties (chaucha, fripapa and superchola) in Carboncillo sector, canton of Saraguro. A CRBD (Completely Randomized Block Design) was used with nine treatments and four repetitions with a total of 36 experimental units. For data analysis, an ANOVA analysis of variance was performed, with Pearson comparisons in Infostat 2019 free version. Variables such as plant height, number of tubers per plant, weight of tubers per plant and yield were analyzed. The treatments with the dose of 0 and 25 kg ha-1 of the fossilized algae plus 10-30-10 in the superchola variety presented the best yield with 66133.6 and 71095.6 kg ha-1. Respectively, the results obtained in the trial reinforce the use of organic fertilizers, in addition to promoting products that are healthy for humans and environmentally friendly. Keywords: fossilized algae, varieties, yield, chemical fertilization, potato.